Gender Assessment of Youth Business Groups: Female Participation and Characteristics - Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2019)
This working paper is an output from the research project "Youth Business Groups for Sustainable Development: Lessons from the Ethiopian Model" that is funded by Research Council of Norway under the NORGLOBAL2 research program for the period 2019-2022. This working paper provides updated and extended information on the gender differences among group members and how these are related to likelihood of becoming group board members and leaders. The study surveyed 274 groups in the period January-May 2019. 28 of the 274 groups have been dissolved by February 2019 for various reasons (internal conflicts, no land provided, low returns to their activity, migration, lack of motivation among members). Lack of support from the local authority was given as the main reason for groups being dissolved (23 of 28 groups). This means that close to 90% of the business groups are still active. Most of the statistics we present below are for the remaining 246 active groups that we intend to include in the training experiments (including control groups) and follow up surveys. Average group size in February 2019 for the 246 active groups was 17.6 members with group sizes varying from 7 to 175 members. The average number of male members was 10.9 against 6.7 female members. 41.4% of the male and 23.6% of female surveyed members are board members. 12.7% of the male and 1.1% of the female surveyed members were group leaders. Only 30.8% of the female members compared to 72.3% of the male members owned a mobile phone at the time of the survey. This puts females in a more disadvantaged position as the mobile phones are important for within-group communication and organization of group activities.
Keywords: D02; D23; 330; Land-poor rural youth; youth business groups; gender composition; female participation; Ethiopia